Letter to the god of love (1399): the first literary quarrel set up by a woman to be found in the French language - Maria Ascenção Ferreira Apolonia (Acta Scientiarum. Language and Culture, 2015)
Letter to the god of love (1399) is the first literary quarrel surprisingly set up by a woman to be found in the French language. Christine de Pizan goes to the palace court to stand for women by replying against the misogyny present in Roman de la rose [The Romance of the Rose]. It is our aim to analyze Christine de Pizan’s discourse in the Middle Ages context. Due to the long time elapsed from that context and ours, we have included some biographical and historical data. She makes herself heir of the Courts of love in which ladies took on the role of magistrates. The letter carries the force of a sentence passed by a judge who has completed judging the offence, culminating with the instruction that the verdict shall be executed. From the magistrate do the teaching role, Christine carries on the Christian civilizing process by proposing new forms of relationship between men and women. The outstanding quality of the author is seen in her ability to conduct the contention and in bringing to light the sophisms included in her opponent’s thesis. In accordance with the scholastic dialectical method, she gives the floor to her opponents but is the one who rules the polyphony.The Letter moves beyond the Court setting to reach the French society, gaining supporters and enemies.